Assessment of psychological personality traits in transgender groups using the Minnesota multiphasic personality inventory - Liu, Yan; Wang, Zhanqiang; Dong, Hanwen; Zhang, Yueqian; Yang, Kebing; Yang, Qingyan; Wang, Zhiren; Niu, Yajuan (Frontiers in Psychology, 2024)
Objective To explore the psychological personality characteristics of transgender groups and to determine whether these characteristics differ according to sociodemographic factors. Methods This cross-sectional study was conducted between January 2021 and April 2023 at a psychosexual outpatient clinic in a psychiatric hospital in Beijing, China. In total, 481 individuals were included in this study, and demographic information was collected using a self-administered general questionnaire. Psychological personality traits were assessed using the Minnesota Multiphasic Personality Inventory (MMPI). Results The mean scores of the assigned male at birth (AMAB) group were significantly higher than those of the male controls for all 10 clinical factors of the MMPI (p < 0.01 or p < 0.001). The scores for both the Masculinity-femininity (Mf) and Depression (D) factors in the AMABs group exceeded the clinical threshold (T > 60) and were the highest and second-highest scores on the entire scale, respectively. Individuals assigned female at birth (AFAB) had significantly higher scores than female controls for Hysteria (Hy), Psychopathic Deviate (Pd), and Hypomania (Ma) (p < 0.05, p < 0.01, and p < 0.001, respectively). There were significant differences in the rates of abnormal values for the various factors of the MMPI (T > 60) according to gender, age, and education (p < 0.05, p < 0.01, and p < 0.001, respectively). Compared to AFABs, AMABs had higher rates of abnormal scores (T > 60) on the Hypochondriasis (Hs), D, Hy, Mf, Paranoia (Pa), Psychasthenia (Pt), Schizophrenia (Sc), and Social Introversion (Si) scales (p < 0.05, p < 0.01, and p < 0.001, respectively). Second, the transgender group aged ≤25 years had higher rates of abnormal scores (T > 60) on the Hs, D, Hy, Pd, Pa, Pt, Sc, and Ma scales (p < 0.05, p < 0.01, and p < 0.001, respectively). Finally, outliers (T > 60) for the Hs, D, Hy, Pd, Pa, Pt, Ma, and Si factors were more prevalent among those with a primary to high school level of education (p < 0.05, p < 0.01, and p < 0.001, respectively). Conclusion Assigned male at births may have a variety of psychological vulnerabilities, and there is a need to focus especially on those with a primary to high school level of education, those aged ≤25 years, and transgender females.